The current UP BLIS program and non-LAM information work a comparison of acquired and required skills and competencies - De Jesus, Annelle Fiona B. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Today, there are new and emerging information professions in the Philippine job market, which are divergent from traditional library, Archives and Museum (LAM) work. This research determined the types of information work outside the LAM setting assumed by the graduates of the University of the Philippines Diliman School of Library and Information Studies (UPSLIS). This also identified discipline-specific and generic competencies required by such professions. This then assessed the current undergraduate program of UP SLIS against such required skills to gauge if the competencies necessary for non-LAM information work were adequately covered or taught in the UP Bachelor of LIS program. The study was facilitated through a semi-or structured survey that was administered via Google Forms. A total of twenty-two participants who belonged to UP SLIS classes of 2011 to 2018 were gathered for the research, with each batch having at least two representative participants.